Architecture and Asceticism: Cultural interaction between Syria and Georgia in Late Antiquity - Loosley Leeming, Emma (Texts and Studies in Eastern Christianity, 2018)
In Architecture and Asceticism Loosley Leeming explores the links between Syria and Georgia in late antiquity. The book takes an inter-disciplinary approach and examines the question from archaeological, art historical, historical, literary and theological viewpoints. Readership: This work is aimed at specialists in Oriental and Eastern Christianity, Late Antique material culture, Syrian (and Syriac) Studies, Kartvelology, Byzantine Studies, Sassanian Studies and Late Antique Levantine and Caucasian issues.